2015
DOI: 10.3390/en8010370
|View full text |Cite
|
Sign up to set email alerts
|

Altering Kinetic Energy Entrainment in Large Eddy Simulations of Large Wind Farms Using Unconventional Wind Turbine Actuator Forcing

Abstract: In this study, horizontally periodic large eddy simulations (LES) are utilized to study turbulent atmospheric boundary-layer flow over wind turbines in the far-downstream portion of a large wind farm where the wakes have merged and the flow is fully developed. In an attempt to increase power generation by enhancing the mean kinetic energy (MKE) entrainment to the wind turbines, hypothetical synthetic forcing is applied to the flow at the turbine rotor locations. The synthetic forcing is not meant to represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…In practice, this can be achieved either through individual pitch control, tilt control or through yaw control [15]. Notwithstanding the fact that individual pitch control and, to a lesser extent, tilt control both show potential for increasing power and/or reducing loads [16][17][18], we will focus on wake redirection for power optimization through yaw control in the remainder of this discussion. Although nominally wind turbines are operated such that the rotor is perpendicular to the incoming flow, an intentional yaw misalignment can be used to induce transversal forces on the incoming flow.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, this can be achieved either through individual pitch control, tilt control or through yaw control [15]. Notwithstanding the fact that individual pitch control and, to a lesser extent, tilt control both show potential for increasing power and/or reducing loads [16][17][18], we will focus on wake redirection for power optimization through yaw control in the remainder of this discussion. Although nominally wind turbines are operated such that the rotor is perpendicular to the incoming flow, an intentional yaw misalignment can be used to induce transversal forces on the incoming flow.…”
Section: Introductionmentioning
confidence: 99%
“…Given the complexity of the aerodynamic interactions between turbines, more work is needed to develop effective controls for secondary frequency regulation. This area of research is just beginning to be explored by studying the potential for control using time‐dependent models and aerodynamic control variables, such as thrust modulation through pitch or generator torque control, yawing or tilting. Receding horizon control techniques have been used successfully for similar problems, including drag reduction in turbulent boundary layers and power maximization of wind farms.…”
Section: Introductionmentioning
confidence: 99%
“…The Reynolds stress component, R12, or the statistical correlation between u' and v', is an indicator of the meandering behavior of the wake; the correlation between u' and w', i.e., R13, can be used to understand the entrainment from more energetic regions of the ABL above the turbine and wake region. This has been discussed extensively in the work by VerHulst and Meneveau [19]. The combined effect of the self-correlation of fluctuations in different velocity components (Rii) is a proportional measure of the turbulent kinetic energy (TKE).…”
Section: Wake Turbulencementioning
confidence: 99%
“…Load statistics, spectra, and wavelet analysis representations for different space and time resolutions were studied. VerHulst and Meneveau [19] studied the kinetic energy entrainment in a large wind farm using LES and the lower-order actuator disk method. They found that synthetic vertical forcing at the turbines can have a significant effect on the power extraction and the mean kinetic energy entrainment in a large wind turbine array.…”
Section: Introductionmentioning
confidence: 99%